Identifikasi Penyebaran Zona Mineralisasi Endapan Timah Menggunakan Metode Induksi Polarisasi Konfigurasi Dipole - Dipole Di Bukit Sambunggiri Kecamatan Merawang Kabupaten Bangka - Rafi Sasena; Guskarnali Guskarnali; Delita Ega Andini (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2019)
Tin is one of the many mining products found in the Bangka Belitung Islands region. Geophysical exploration was carried out in the Bukit Sambunggiri area, Merawang District, Bangka Regency using the dipole-dipole configuration polarization to detect polarizationel ectricity on surface of metal material and induction method to identify the distribution of tin deposit mineralization. The parameters is measuring area of ​​21 Ha with 6 tracks, length A, B, C is 640 meters, D, E, F is 840 meters, spacing between tracks 50 meters, spacing between electrodes 10 meters and equipment used is Multy Channel RS / IP Supersting. Processing measurement data using Res2dinv software to create 2D cross sections and Montaj Oasis for 3D cross sections. The results of resistivity and chargeability data processing of a total of six trajectories have 3 trajectories which have a clear mineralization area, that is, A trajectory is assumed to be at a distance of 250 - 350 meters and depths from 0 - 50 meters which are characterized by medium-high chargeability - 30) msec and low resistivity (<700) Ohm.m. On track D, it is estimated that there are three parts at a distance of 100 - 220 meters in depth of 50-50 meters, distance of 335 - 440 meters in depth of 50-130 meters and distance of 590 - 680 meters in depth of 50-130 meters. 430 meters at a depth of 0 - 150 meters. The results of interpretation of track A to track C are suspected to have zones of tin mineralization with secondary deposits and it is known that the mineralized zone is thought to be located below the bog iron zone with secondary tin deposits. This is due to the fact that the bog iron is hard rock like granite which is oxidized, so minerals that have a high level of resistance to weathering such as cassiterite and quartz will be released from the rock body and deposited in the lower layer. While path D to trajectory F is suspected to be the continuation of the zone of tin mineralization with primary deposits. This is presumably because the location of the mineralization area spreads between intrusion of granite rocks which have a high chargeability and resistivity value.